Flagellia, a new subgenus of Haliclona (Porifera, Haplosclerida) - Van Soest, Rob W.M. (European Journal of Taxonomy, 2017)
Haplosclerid sponges possessing a unique asymmetric flagelliform type of sigmoid microsclere have been reported from all global oceans. This peculiar spicule, characterized by a circular or elliptical shape, with a longer and sharper curved ending at one side and a shorter and more gradually curved ending at the opposing side, is proposed to be termed ‘flagellosigma’. These sponges invariably also possess smaller normal sigmas while their skeletal structure of oxea megascleres is markedly confused. They are assigned to the large genus Haliclona Grant, 1841 (family Chalinidae) in a new subgenus, Haliclona (Flagellia) subgen. nov. The species belonging to the new subgenus are reviewed and four species new to science are described, Haliclona (Flagellia) indonesiae subgen. et sp. nov., H. (F.) amirantensis subgen. et sp. nov., H. (F.) hiberniae subgen. et sp. nov. and H. (F.) hajdui subgen. et sp. nov. One species, H. (F.) hentscheli nom. nov., is given a new name on account of secondary homonymy caused by its transfer to the genus Haliclona. One species remains unnamed because of paucity of material. Already known species, reassigned to the new subgenus are H. (F.) hamata subgen. et comb. nov., H. (F.) flagellifera subgen. et comb. nov., H. (F.) porosa subgen. et comb. nov., H. (F.) edaphus subgen. et comb. nov. and H. (F.) anataria subgen. et comb. nov. Additional species are likely hiding among many erroneous records of ‘Gellius flagellifer’ from wide ranging parts of the global oceans.